IPTEKS EFEKTIVITAS PENGOLAHAN DATA WAJIB PAJAK DENGAN APLIKASI PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Mandagi, Jaquline; Wangkar, Anekke (Universitas Sam Ratulangi, 2018)
Tax has great benefits for the development of the Indonesian nation. This is because taxes are the biggest potential revenue in the country. Because taxes are direct receipts that can be processed to finance various kinds of state needs. Seeing the rapid development of technology, the Directorate General of Taxes (DGT) uses technology as an alternative channel of communication with tax payers. Therefore the Pratama Tax Office Manado relies heavily on Digital Technology in the form of electronic media and social media to facilitate processing of taxpayer data. The purpose of this study is to find out the effective processing of data with applications (software) under the supervision of the Directorate General of Tax Information System in collecting taxpayers at the Manado tax service office. Electronic media can be used to disseminate information relating to socialization, counseling and as a means of communication to the WP used by the DGT through socialization, letters, e-mail, websites and call centers. With the use of technology can improve work effectiveness, save time, effort and thought, and accelerate the flow of information for leaders to make decisions.Keywords: effectiveness, tax, technology, application